HRM Strategic Fit: Introducing Alternatives to Improve Performance in public organizations - Alamri, Mashhoor (The Arab Journal of Administration, 2019)
Growing scientific research has shown the importance of internal and external strategic fit of human resources. However, the impact of the HRM strategic fit on the organizational performance of government agencies has not been adequately researched. This paper addresses the question of whether strategic fit of human resources explains organizational performance. To address this problem, the study aimed to identify whether the HRM strategic fit explains the organizational performance of government agencies. To collect the data, 67 questionnaires were distributed to the human resources managers of these agencies through public relations departments. After the data collection and analysis, the study found that if the human resources strategy and the organization’s strategy were to match the role and position of human resources in senior management and the alignment of HR strategy with other key organizational strategies, organizational performance would improve. The study did not, however, support the hypothesis that internal compatibility of human resources functions may lead to improved organizational performance. These results will be useful for leadership in government agencies in three important themes: the need to involve human resources management in the organization strategic planning process, giving HRM mangers the appropriate position to suit the important role the play, and ensure that HR functions and policies are integrated with the other organization functions. otherwise the efforts of organizational performance will not bear its fruit.